INCREASING THE CAPACITY OF COMMUNITIES IN RECOVERY PROJECTS THROUGH ENERGY EFFICIENCY TRAINING - ЛІСОВИК, В. Л.; ШЕВЧЕНКО, О. М.; ШОВКАЛЮК, М. М. (Technologies and Engineering, 2025)
Introduction. One of the challenges for Ukraine in the current conditions is the quick and professional implementation of reconstruction projects in territorial communities affected by military aggression. In addition, our state has international obligations in the field of energy and environmental security, therefore recovery is inextricably linked with energy efficiency improvement projects and the development of energy management systems. Thus, municipalities need qualified specialists with relevant knowledge and competences. Purpose. Increasing the capacity of cities to participate in restoration projects by developing the competences of specialists of territorial communities in matters of planning and implementation of energy-efficient projects. Development of the capacity of communities to achieve climate neutrality and dissemination of experience gained in the development and implementation of energy-efficient projects within the framework of the recovery of Ukraine. Methodology. The research included interviewing specialists of territorial communities, performing an analysis of their needs and further drawing up a training program. During the training, active methods were used, which develop both professional skills for solving specialized tasks of managing and supporting projects during the life cycle ("hard skills"), and extra-professional competencies ("soft skills"). The following research methods were used: SWOT analysis, technical and economic analysis, modeling, a systematic approach to project management taking into account the life cycle. Findings. recommendations and document templates for the creation of a project implementation group were developed, a training program for municipal specialists was developed, which includes lectures, practical exercises, individual and group tasks, interactive business games, testing, independent work, exchange of experience. Organized training for representatives of territorial communities; as part of the implementation of an "end-to-end" independent task, technical and economic feasibility studie) were developed for 12 communally owned buildings. Originality. Based on the analysis of community needs, topics for training were formulated and a training program was developed for groups implementing energy efficiency improvement projects in Ukrainian cities. The procedure and recommendations for conducting group and individual practical exercises, business games, and performing independent tasks according to the recommended template are formulated. All this contributes to the development of the competences of specialists of territorial communities in matters of planning and implementation of restoration projects, which are inextricably linked with the issues of increasing energy efficiency and energy sustainability of cities. Practical value. Different methods of active learning have been developed, adapted for territorial communities and implemented. Recommendations for the creation of a group for the implementation of demo projects, forms of questionnaires for collecting initial information, templates of necessary documents for the implementation of projects (feasibility study, technical tasks for three types of projects (SPP roof/ground, introduction of frequency-regulated electric drive), forms for monitoring, check sheets.